The Termite (Subterranean Macrotermes carbonarius) attack Rating of Thermally Treated Teak (Tectona grandis L.f.) Plywood : Thermal treatment of wood modification - Bouaphavong, Douangta; Jarusombuti, Songklod; Veenin, Teera; Phonetip, Khamtan; Soukphaxay, Khonethong; Khamboudaphan, Somxay (วารสารวนศาสตร์ไทย, 2023)
Thermal treatment on teak veneer has been recognized as the improved biological property protection method of teak-plywood product from the termite attacking. The objective was investigated how much rating of teak plywood that attacked by termite at the different level of temperature and length of time. The temperatures were at the control, 180, 200, 220, and 240 °C applied at three different lengths of time, i.e., 4, 8, and 12 min on teak veneer sheets. The plywood production was applied two type adhesives with Phenol formaldehyde PF and Urea Formaldehyde UF, both samples was placed in the ground (50 cm deep, 50 cm width and 5 m length with contact with termite home). As the results showed the evidence attacked by termite at different level of temperature at 220 and 240 °C on 4, 8, and 12 min was significant different it is increased as per the temperature in both adhesives. Thermal treatment veneer at 220 and 240 °C can protected termite attacking on teak plywood product as well.